Market Sensing Capability and Customer Relationship Management on Marketing Performance: Role E-Marketing Strategy - Mulyana Mulyana; Mohammad Azka (Jurnal Manajemen Indonesia, 2022)
This study aims to investigate the effect of market sensing capability (MSC), customer relationship management (CRM) and Electronic-marketing strategy (e-MS) on marketing performance (MP). This study tries to solve the gap between market sensing capability and marketing performance. Respondents of this study were 192 owners or leaders of Muslim fashion SMEs in Central Java. A hierarchical regression analysis was used for data analysis. The results showed that market sensing capability and customer relationship management have a significant effect on e-marketing strategy and marketing performance. Furthermore, e-marketing strategy can mediate the relationship between market sensing capability and customer relationship management with marketing performance. Keywords—Market Sensing Capability; Customer Relationship Management; e-Marketing Strategy; Marketing Performance